A new species of the genus Scoparia Haworth, 1811 (Lepidoptera: Crambidae) from the Northeast Caucasus - Tsvetkov, Eugene (Zootaxa, 2025)
Scoparia dagestanica sp. nov. is described from the republic of Dagestan, South Russia. Male and female genitalia of the species and habitus of imago are illustrated. The new species is well distinguished from its congeners by genitalia of both sexes. The description is based on material collected by the author in Dagestan in 2022–2024.